Analysis of an optimal cluster approach: a review paper. Issue 1 (1st January 2023) - Jollyta, Deny; Efendi, Syahril; Zarlis, Muhammad; Mawengkang, Herman
Abstract: Determining the optimal clusters can be regarded as a grouping problem that has produced many cluster approach methods in various studies. Each method has provisions that can solve one or more grouping problems in generating information from data set with a number of k being tested. The advantages and disadvantages of each method actually complement to each other in solving the grouping problems. This paper aims to describe the performance of cluster approach methods in determining the optimal clusters through a review by paying attention to the criteria of the problem which is an obstacle to the grouping problem. The results of this review are expected to be a reference for developing the new optimal cluster approach method through possible combinatorial optimization.